Effects of stocking density and salinity on growth and survival of red tilapia, Oreochromis sp. fry - Abd. Razak, Muhammad Hafis (2013)
Oreochromis sp. has become increasingly popular because it’s similar appearance to marine red snapper and contributes approximately 90% of the total production of freshwater fish in Malaysia. The aim of this study were to determine the length and weight increment of Oreochromis sp. fry reared at different stocking densities and effects of different salinities on the growth and survival. This study was conducted at the Aquaculture Research Station in University Putra Malaysia, Puchong, Selangor. First study was stocking densities, three different stocking densities used were 50, 100 and 150 fry/L. Second studies, four different salinities used were 0, 3, 6 and 9 ppt. Each treatment was prepared in three replications. Arrangements of the treatment were randomly. Every 3 day the data of water parameter were collected before water changes. The experiments were tested by using one way ANOVA analysis of variance and comparison between treatments with Duncan test. The length and weight of fry was measured once a week until 4 week cultured period. Results showed that 50 fry/L was the significantly highest (P<0.05) in weight increment, total length (TL) and survival. 3 ppt of salinity was the significantly highest (P<0.05) salinity in this experiment followed by 0, 6 and 9 ppt. Oreochromis sp. fry had a better growth in 50 fry/L in stocking densities and growth well in 3 ppt of salinity without any adverse effect.